Digital Fatwā Issuance Mechanisms in Southeast Asia: Challenges and Opportunities for Harmonizing Sharia and Contemporary Society - Moch Nurcholis Majid; Iwan Setiawan Wibisono (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
The rapid expansion of digital platforms has transformed the issuance of fatwa in Southeast Asia, enabling Islamic legal opinions to be accessed widely and quickly. This shift challenges traditional patterns of religious authority, which were previously centered around formal institutions and face-to-face scholarly deliberation. While digital fatwa mechanisms enhance accessibility and responsiveness, they also raise concerns about legitimacy, legal accuracy, and public trust. This study examines the effectiveness of digital fatwa issuance mechanisms in Malaysia, Indonesia, and Brunei Darussalam, using a qualitative comparative research approach. Data were collected through content analysis of official digital fatwa portals, focusing on accessibility, authority, validation, and legal consistency. The findings reveal that digital platforms increase access speed and broaden public reach, enabling religious institutions to address emerging legal issues more effectively. However, variations in verification procedures and legitimacy frameworks across countries reflect differences in governance and state involvement. Key challenges include the authentication of mufti authority, standardization of ijtihad methodologies, and consistency in legal substance. Digital fatwa contribute to improving Islamic legal literacy but risk authority fragmentation due to the proliferation of digital sources. The study concludes that integrating the efficiency of digital platforms with the authoritative safeguards of traditional institutions is crucial for developing an accountable model of digital fatwa governance.